Immobilization of Ntn hydrolases on APTES fuctionalized SBA-15 - Shah, Pallavi; Sridevi, N.; Prabhune, Asmita; Ramaswamy, Veda (From Zeolites to Porous Mof Materials: the 40th Anniversary of International Zeolite Conference, Proceedings of the 15th International Zeolite Conference, 2007)
APTES Functionalized mesoporous silica SBA-15 molecular sieves have been prepared and used for immobilization of Penicillin G acylase. Physico chemical characterization was done by nitrogen adsorption, powder XRD and TEM methods to understand the nature of immobilized PGA enzyme. XRD data indicate a good mesoscopic order. The characteristic hexagonal features of SBA-15 were maintained in PGA immobilized SBA-15 samples. Incorporation of PGA does not affect the original pore structure of the parent SBA-15. The adsorption of PGA on SBA-15 from buffered solutions with a pH value, 7.8 has been studied as a model protein adsorption system. The maximum activity of the immobilized enzyme was observed at pH 7.8, slightly below the isoelectric point of the enzyme. The loading capacity of immobilized PGA is 34 mg protein per 0.5 g of SBA-15. The stability of Penicillin G acylase was enhanced by the physical entrapment in SBA-15.
15th International Zeolite Conference, Beijing, PEOPLES R CHINA, AUG 12-17, 2007

Immobilization of penicillin G acylase on amino functionalized mesoporous silica - Sridevi, N.; Pallavi, Shah; Asmita, Prabhune (Research Journal of Biotechnology, 2008)
Penicillin G acylase was immobilized on Amino functionalized mesoporous silica by adsorption method. In this paper we present the effect of penicillin G acylase immobilization on amino-functionalized mesoporous silica and the effect of silica as host matrix on enzyme kinetics. The loading capacity of immobilized Penicillin G acylase is 34 mg protein per 0.5 g of SBA-15. About 65% of the protein was adsorbed on mesoporous silica. The stability of penicillin acylase was enhanced after immobilization on mesoporous silica. The adsorbed enzyme is more stable than the soluble form, both to temperature and pH environments and retained 73% of its activity.
Keywords: Amino functionalized mesoporous silica; Immobilization; Penicillin G acylase; pH and temperature stabilities

Structural features of Penicillin acylase adsorption on APTES functionalized SBA-15 - Shah, Pallavi; Sridevi, N.; Prabhune, Asmita; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2008)
The immobilization of Penicillin acylase (PGA) enzyme (which belongs to the Ntn hydrolase super family) into the amino-functionalized SBA-15 mesoporous molecular sieve is carried out to see the effect of silica as a host matrix on the enzyme kinetics. Physicochemical characterization by nitrogen adsorption, powder XRD and TEM methods indicate that the characteristic hexagonal features and the original pore structure of the parent SBA-15 is retained even after the incorporation of PGA. The adsorption of PGA on SBA15 shows a dependence on the pore volume and the composition of the adsorbent. The maximum loading of the enzyme was observed at pH 7.8, slightly below the isoelectric point of the enzyme. The loading capacity of immobilized PGA is 34 mg protein per 0.5 g of SBA-15. The trapped enzyme is more stable than the soluble form to temperature and pH environments and retained 73% of its activity after immobilization. This enhanced stability is attributed to the protective nature of the cage itself and to the rigidity of the SiO(2) matrix, which reduces the freedom of peptide-chain refolding of molecular motions that occur in denaturation processes. The strength of binding is very strong; however, the activity of the immobilized enzyme is then simply restored with very little leakage of enzyme from the support. An important feature of the immobilized PGA enzyme is the excellent reusability without significant loss in activity, which indicates potentially exciting industrial/biomedical application of this support. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Penicillin G acylase; PGA immobilized SBA-15; pH and temperatures stability; SBA-15

Brevibacillus sp: a novel thermophilic source for the production of bile salt hydrolase - Sridevi, N.; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2009)
A thermophilic microorganism growing within the temperature range of 40-65 A degrees C (optimum at 55 A degrees C) was isolated from hot water springs near Konkan, Maharashtra, India. Based on 16S rDNA sequence analysis, it was concluded that the isolate belongs to the genus Brevibacillus. The present paper reports the isolation, identification, and standardization of fermentation conditions for the production of enzyme, bile salt hydrolase (EC 3.5.1.24) which is produced intracellularly at high temperatures. This is the first report regarding the production of bile salt hydrolase from a thermophilic source. Optimization of fermentation conditions resulted in a 2.9-fold enhancement in enzyme production.
Keywords: Bile salt hydrolase; Brevibacillus sp; Fermentation; Glycodeoxycholic acid; Hot springs; Thermophile

Characterization of the smallest dimeric bile salt hydrolase from a thermophile brevibacillus sp. - Sridevi, N.; Srivastava, Sameer; Khan, Bashir Mohammad; Prabhune, Asmita Ashutosh (Extremophiles, 2009)
A thermophilic microorganism producing bile salt hydrolase was isolated from hot water springs, Pali, Maharashtra, India. This microorganism was identified as Brevibacillus sp. by 16S rDNA sequencing. Bile salt hydrolase (BSH) was purified to homogeneity from this thermophilic source using Q-sepharose chromatography and its enzymatic properties were characterized. The subunit molecular mass of the purified enzyme was estimated to be 28 kDa by SDS-PAGE and, 28.2 kDa by MALDI-TOF analysis. The native molecular mass was estimated to be 56 kDa by gel filtration chromatography, indicating the protein to be a homodimer. The pH and temperature optimum for the enzyme catalysis were 9.0 and 60A degrees C, respectively. Even though BSH from Brevibacillus sp. hydrolyzed all of the six major human bile salts, the enzyme preferred glycine conjugated substrates with apparent K (M) and k (cat) values of 3.08 mu M and 6.32 x 10(2) s(-1), respectively, for glycodeoxycholic acid. The NH2-terminal sequence of the purified enzyme was determined and it did not show any homology with other bacterial bile salt hydrolases. To our knowledge, this is the first report describing the purification of BSH to homogeneity from a thermophilic source.
Keywords: Bile salt hydrolase; Brevibacillus sp.; Dimeric intracellular enzyme; Purification; Thermophile

Hypocholesteremic effect of bile salt hydrolase from Lactobacillus buchneri ATCC 4005 - Sridevi, N.; Vishwe, Pradnya; Prabhune, Asmita (Food Research International, 2009)
The effect of oral administration of the immobilized bile salt hydrolase enzyme on serum cholesterol. triglyceride, high density lipoprotein levels and its application in the therapeutic treatment of hypercholesteremia was assessed. Culture conditions were optimized for the production of bile salt hydrolase, which resulted in 2.9-fold enhancement in activity. Bile salt hydrolase (BSH; E.C.3.5.1.24) was isolated from Lactobacillus buchneri ATCC 4005 and immobilized in 0.5% gellan gum gel. The immobilized enzyme was orally delivered in wistar rats, induced with hypercholesteremia by triton X-100. The serum cholesterol and triglycerides were reduced by 50% and 15%, respectively, in the group fed with immobilized enzyme 10 IU/kg dose whereas administration of 20 IU/kg immobilized enzyme resulted in reduction of serum cholesterol by 58% and triglycerides by 45%, respectively. The results indicate that bile salt hydrolase has potential cholesterol lowering property and oral administration of the immobilized enzyme is an alternative pharmacological approach to reduce serum cholesterol levels. (C) 2009 Elsevier Ltd. All rights reserved.
International Congress on Bioprocesses in Food Industries, Hyderabad, INDIA, NOV 06-08, 2008
Keywords: Bile salt hydrolase; Gellan gum; Hypocholesteremic effect; Lactobacillus buchneri; Wistar Rats

Immobilization of bile salt hydrolase enzyme on mesoporous SBA-15 for co-precipitation of cholesterol - Bhange, Pallavi; Sridevi, N.; Bhange, Deu S.; Prabhune, Asmita; Ramaswamy, Veda (International Journal of Biological Macromolecules, 2014)
We describe herein a simple and effective strategy for immobilization of bile salt hydrolase enzyme by grafting glutaraldehyde groups inside channels of APTES functionalized SBA-15. The increase in glutaraldehyde concentration prevents leakage of enzyme but showed a steep decrease in enzyme activity in the immobilized matrix. So the degree of cross-linking should be the minimum possible to ensure sufficient stability without loss of activity. Cross-linking carried out with 0.1% glutaraldehyde concentration showed the highest activity, so this was used in all further experiments. Physico-chemical characterizations of the immobilized enzyme were carried out by XRD, N-2 adsorption, TEM, FUR and Si-29 CP-MAS NMR techniques. Immobilized BSH exhibits enhanced stability over a wide pH (3-11) and temperature range (40-80 degrees C) and retains an activity even after recycling experiments and six months of storage. From our in vivo research experiment toward co-precipitation of cholesterol, we have shown that immobilized BSH enzyme may be the promising catalyst for the reduction of serum cholesterol levels in our preliminary investigation. Enhancement in pH stability at the extreme side of pH may favor the use of immobilized BSH enzyme for drug delivery purpose to with stand extreme pH conditions in the gastrointestinal conditions. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Bile salt hydrolase; Co-precipitation of cholesterol; SBA-15